2008
DOI: 10.1103/physreve.77.046107
|View full text |Cite
|
Sign up to set email alerts
|

Nature of packs used in propellant modeling

Abstract: In recent years we have constructed closely packed spheres using the Lubachevsky-Stillinger algorithm to generate morphological models of heterogeneous solid propellants. Improvements to the algorithm now allow us to create large polydisperse packs on a laptop computer, and to create monodisperse packs with packing fractions greater than 70% which display significant crystal order. The use of these models in the physical context motivates efforts to examine in some detail the nature of the packs, including cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…For example, higher growth rates reduce the packing capability while slower ones enable higher packing fractions. In this respect, close-pack condition represents an asymptotic state that can be reached only after an infinite simulation time [27]. The simplest possible stopping criterion consists of comparing f against a target packing fraction.…”
Section: Packing Fraction and Stopping Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, higher growth rates reduce the packing capability while slower ones enable higher packing fractions. In this respect, close-pack condition represents an asymptotic state that can be reached only after an infinite simulation time [27]. The simplest possible stopping criterion consists of comparing f against a target packing fraction.…”
Section: Packing Fraction and Stopping Criteriamentioning
confidence: 99%
“…Rocpack [20]). The comparison with experimental tomographic data through spatial statistics for some of the aforementioned techniques have demonstrated that different algorithms do not always generate equivalent microstrucures [27].…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of inclusion shape on the effective material properties, the packing code Rocpack [61][62][63] is used to generate statistically isotropic systems of Platonic solids. The algorithm is a hybrid of the Lubachevsky-Stillinger [44] and Adaptive Shrinking Cell [64,65] packing algorithms, where infinitesimal particles are randomly distributed within a volume and allowed to grow until a desired volume fraction is reached.…”
Section: (I) Generation Of Microstructuresmentioning
confidence: 99%
“…These microstructures can allow trends in material behavior to be explored. More realistic generation of 3D microstructures (see, e.g.,) 46,47 is not the focus of this study. Regardless, the simulation framework adopted here lends itself to studies which could use microstructures generated using other methods.…”
Section: Energetic Molecular Crystalsmentioning
confidence: 99%